Characterization of hydrochar produced from dairy manure for the purpose of land applications - Imran Hussain Mahdy; B. Brian He (Environment Conservation Journal)
Hydrochar produced from dairy manure has unique morphology and surface properties and contains a substantial amount of macro- and micro-nutrients,  including a high phosphorus (P) content, which may relate to its applications as an organic fertilizer for nutrient cycling. The objective of this study was to evaluate the physiochemical properties of hydrochar produced from dairy manure at five  processing temperatures. Hydrochar was produced from dairy manure via hydrothermal carbonization (HTC) at operating conditions of 195-255 ℃, 60 min of  processing time, and 10% solid manure content. The hydrochar characteristics were examined by elemental analysis, Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and inductively coupled plasma (ICP). The findings from FTIR revealed that the surface of hydrochar was enriched with oxygen-containing functional groups, which is beneficial in holding moisture and nutrients. The surface area of hydrochar samples ranged from 3.66 to 6.01 m²/g. The total P and nitrogen (N) content peaked at 17,333 and 22,600 mg/kg at 255°C, respectively, while the highest potassium (K) content of 2,467 mg/kg was observed at 180°C. The findings from this study would contribute to a better understanding of hydrochar for nutrient cycling and soil improvement, thus for more sustainable and effective agricultural practices.